Respuesta :

Answer: -12 x^2 - 3x + 27  

In this question, there are two function of f(x) and g(x) 
f(x)= -9 x^2 - 7x + 12
g(x)= 3x^2 -4x -15
The question is about f(x)- g(x). To answer this, you just need to replace the question with the function. Don't forget to apply the minus to all the product inside the function. The calculation would be:

f(x)- g(x)= 
(-9 x^2 - 7x + 12) -(3x^2 -4x -15)=
-9 x^2 - 7x + 12 (-3x^2 +4x +15)= 
-12 x^2 - 3x + 27  

Answer:

-12x2 - 3x + 27

Step-by-step explanation: